The determinants of Euro Zone government credit spreads - Jesus, Carlos Alberto Alves de (2010)
This paper studies the determinants of the Euro Zone government credit spreads. We analyzed the sensitivity of credit spread changes to financial and macroeconomic variables. We used the popular parameterization of the zero-coupon yield curve introduced by Nelson and Siegel (1987) in order to estimate the term structure of interest rates for seven EMU countries from January 2000 to December 2005. Sovereign credit spreads are computed from each of the countries against Germany, which was considered as the EMU benchmark. Subsequent analysis is made following Van Landschoot (2004) and Dullmann et al. (2000). Results suggest that the level of spot interest rates and the slope of the yield curve are statistically significant explanatory variables of credit spread changes, whereas other macroeconomic and market related variables present mixed conclusions. Panel data analysis shows that there is no evidence of different responses to credit spread changes across countries.